Preparation and application of photoelectrochemical sensor based on NYF-TiO2-Ti3C2 composite material
Through the photoelectrochemical sensor based on NYF-TiO2-Ti3C2 composite material, the existing D-serine detection method is solved, and high sensitivity and selective detection of D-serine is achieved, and the sensor is more sensitive, portable and low-cost.
Patent Information
- Application Number
- CN202210953488.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-10
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2042-08-10
AI Technical Summary
The existing D-serine detection methods have problems such as time-consuming, cumbersome operation and high degree of professionalism, and photoelectrochemical sensors have not been widely used in detecting D-serine.
The composite material was prepared by solvothermal method and the electrode was modified to improve the photoelectrochemical reaction efficiency.
High sensitivity and selective detection of D-serine are achieved, and the sensor is more sensitive, portable and cheap, solving the problem of insufficient application of photoelectrochemical sensors in D-serine detection.
Smart Images

Figure CN115541672B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of photoelectrochemical sensors, in particular to the preparation and application of photoelectrochemical sensors based on NYF-TiO2-Ti3C2 composite materials. Background Art
[0002] D-serine (D-Ser) is the main endogenous ligand of the glycine site on the N-methyl-D-aspartate (NMDA) receptor, and plays an indispensable role in enhancing synaptic plasticity and treating neuropathies and mental disorders. Supplementation of D-ser can not only alleviate the symptoms of cognitive decline, but also alleviate diseases characterized by NMDA signals, such as cocaine dependence, Alzheimer's disease, amyotrophic lateral sclerosis, schizophrenia, etc. Many clinical studies have shown that the concentration of D-ser in the serum of patients with schizophrenia is significantly lower than that of healthy controls, while the level of D-ser in the hippocampus and parietal cortex of patients with Alzheimer's disease (AD) is relatively high. Therefore, the detection of D-ser concentration is of great significance for the diagnosis of early diseases. At present, a variety of strategies for detecting D-ser have been designed, including ion chromatography, capillary electrophoresis, fluorescence spectroscopy, high performance liquid chromatography, etc. However, these methods have one or more disadvantages, such as time-consuming, cumbersome operations, and high degree of specialization, which hinder their widespread application.
[0003] Photoelectrochemical (PEC) analysis technology is an emerging technology developed based on the principle of light-to-electron conversion. It has attracted people's attention due to its advantages such as high sensitivity, low cost, simple operation and fast response speed. It is understood that the PEC sensing platform for detecting D-ser has not been reported. The performance of PEC biosensors depends largely on the properties of photosensitive materials and the photocurrent signal caused by the target. Therefore, choosing suitable semiconductor materials and designing innovative signal amplification strategies are extremely important for building an excellent PEC biosensor platform for detecting D-ser.
[0004] Lanthanide-doped upconversion nanoparticles (UCNPs) are a new type of material that can convert low-energy near-infrared light into high-energy ultraviolet (UV) or visible light (Vis) through the anti-Stokes process. Not only that, it also has advantages that other materials cannot replace: excellent penetrability, low biotoxicity, low photodamage and high photostability, and is widely used in biomedicine and biochemistry. However, most photosensitive materials can only absorb UV light, and the composite of UCNP and semiconductor is always unsatisfactory in the utilization of light. TiO2-Ti3C2 is a semiconductor material with excellent metallic conductivity and broadband strong absorption. It is combined with NaYF4:Yb / Er by solvothermal method to regulate the composite structure, which can not only improve the separation and transmission efficiency of photogenerated electrons and holes, but also enhance the absorption of light. Therefore, it is of great research significance to develop a photoelectrochemical sensor based on upconversion NaYF4:Yb / Er-TiO2-Ti3C2 (abbreviated as NYF-TiO2-Ti3C2) composite material and broaden its application range. To this end, we proposed the preparation and application of photoelectrochemical sensors based on composite materials. Summary of the invention
[0005] 1. Technical issues to be resolved
[0006] In view of the deficiencies in the prior art, the present invention provides the preparation and application of a photoelectrochemical sensor based on a NYF-TiO2-Ti3C2 composite material to solve the above-mentioned problems.
[0007] (II) Technical solution
[0008] In order to achieve the above-mentioned purpose, the present invention provides the following technical solutions:
[0009] A preparation method of a photoelectrochemical sensor based on a NYF-TiO2-Ti3C2 composite material comprises the following steps:
[0010] Step 1: Multilayer Ti3C2T x The powder was added to a dimethyl sulfoxide solution and stirred. The mixed solution after the reaction was centrifuged and washed to obtain a few-layer Ti3C2T x ;
[0011] Step 2: Prepare NYF-TiO2-Ti3C2 composites by solvothermal method;
[0012] Step 3: Modification of NYF-TiO2-Ti3C2 composite electrode.
[0013] Preferably, the few-layer Ti3C2T x The content is as follows: multilayer Ti3C2T xThe powder was added into dimethyl sulfoxide solution and stirred for 12 h, and then the mixed solution after the reaction was centrifuged and washed to obtain a few-layer Ti3C2T x .
[0014] Preferably, the few-layer Ti3C2T x Before use, it needs to be dispersed in deionized water, sonicated under N2 protection, and then centrifuged to remove the undetached sample and keep the supernatant under N2 protection for later use.
[0015] Preferably, the preparation method of the NYF-TiO2-Ti3C2 composite material is as follows:
[0016] S1: Add YbCl36H2O, YCl36H2O, ErCl36H2O and polyethyleneimine into ethanol and stir to obtain solution A;
[0017] S2: Then the sodium fluoride solution and the few-layer Ti3C2T x Solution A was added to the solution;
[0018] S3: The mixture is then stirred evenly and subjected to a solvent thermal reaction. The mixed solution obtained after the reaction is centrifuged, washed and dried to prepare a NYF-TiO2-Ti3C2 composite material.
[0019] Preferably, the molar ratio of YbCl36H2O, YCl36H2O and ErCl36H2O is 79.8:20:0.2.
[0020] Preferably, the solvent thermal reaction conditions are 220° C. and the reaction time is 10 h.
[0021] Preferably, the washing and drying conditions are washing with deionized water and ethanol, and then placing in a vacuum drying oven at 60° C. for 12 hours.
[0022] Preferably, the modification of the electrode in the third step comprises the following: ultrasonically dispersing the NYF-TiO2-Ti3C2 composite material, drop coating it on clean fluorine-doped indium tin oxide conductive glass, and drying it at room temperature.
[0023] Preferably, the indium tin oxide conductive glass is cleaned with washing powder, acetone, ethanol and ultrapure water in sequence, and then blown dry with nitrogen.
[0024] The application of photoelectrochemical sensors based on NYF-TiO2-Ti3C2 composite materials includes the following: constructing a photoelectrochemical sensor for detecting D-er.
[0025] (III) Beneficial effects
[0026] Compared with the prior art, the present invention provides the preparation and application of a photoelectrochemical sensor based on a composite NYF-TiO2-Ti3C2 material, which has the following beneficial effects:
[0027] 1. The present invention uses corn-shaped NaYF4:Yb / Er as an energy donor, which can convert near-infrared light into visible light that matches the absorption of TiO2-Ti3C2, effectively solving the problems of low light utilization between upconversion materials and semiconductors, easy recombination of photogenerated carriers, and poor stability.
[0028] 2. The NYF-TiO2-Ti3C2 composite material provided by the present invention has good absorption of near-infrared light, high photostability, low biological toxicity and strong penetrability, and can be used to prepare microelectrodes for in vivo detection.
[0029] 3. The NYF-TiO2-Ti3C2 photoelectrochemical sensor provided by the present invention is first used for the highly sensitive and highly selective detection of D-ser. The biosensor is more sensitive, portable and low-cost, opening up a new way for the detection of other biomarkers. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 The scanning electron microscope (SEM), transmission electron microscope (TEM), high resolution (HRTEM) and elemental mapping images of the material prepared in Example 1;
[0031] Figure 2 X-ray diffraction characterization diagrams of NaYF4:Yb / Er (a), TiO2-Ti3C2 (b), and NYF-TiO2-Ti3C2 (c) samples prepared in Example 1;
[0032] Figure 3 X-ray photoelectron spectra of TiO2-Ti3C2 prepared in Example 1 and NYF-TiO2-Ti3C2 provided by the present invention;
[0033] Figure 4 Electrochemical impedance spectroscopy (EIS) diagrams of NaYF4:Yb / Er (a), TiO2-Ti3C2 (b), NYF-TiO2-Ti3C2 (c), and NYF-TiO2-Ti3C2 / DAAO (d) prepared in Example 1;
[0034] Figure 5 Schematic diagram of UV-visible-near infrared spectra of NaYF4:Yb / Er, TiO2-Ti3C2, and NYF-TiO2-Ti3C2 prepared in Example 1;
[0035] Figure 6The fluorescence spectra of NaYF4:Yb / Er and NYF-TiO2-Ti3C2 prepared in Example 1;
[0036] Figure 7 Schematic diagram of the photocurrent response of the photoelectrochemical sensor modified with NaYF4:Yb / Er (a), TiO2-Ti3C2 (b), NYF-TiO2-Ti3C2 (d), and NYF-TiO2-Ti3C2 / DAAO (c, e) in Example 1;
[0037] Figure 8 Schematic diagram of anti-interference test of NYF-TiO2-Ti3C2 / DAAO photoelectrochemical sensor prepared in Example 1;
[0038] Fig. 9 Schematic diagram of the photocurrent response of the NYF-TiO2-Ti3C2 / DAAO photoelectrochemical sensor prepared in Example 1 to different concentrations of D-ser;
[0039] Fig.10 Schematic diagram of the signal stability test of the NYF-TiO2-Ti3C2 / DAAO photoelectrochemical sensor prepared in Example 1. DETAILED DESCRIPTION
[0040] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0041] Example
[0042] The raw materials used in the embodiments of the present invention are as follows:
[0043] Drugs and reagents: Lanthanum chloride complex (LnCl3 6H2O, Ln = Y, Yb, Er, 99.9%), sodium fluoride (99.0%), anhydrous sodium sulfate, polyethyleneimine (PEI) (branched, average MW ~ 10000, 99.0%), ethylene glycol (EG, 99.8%), D-aspartic acid, L-serine, dopamine, L-proline, L-glutamic acid, L-lysine, glutathione, L-threonine, glucose, ascorbic acid, L-histidine were purchased from Aladdin Reagent Database (Shanghai, China). Ti3AlC2 powder, dimethyl sulfoxide (99.0%), and hydrofluoric acid (49% wt%) were purchased from McLean, China. Human serum and porcine kidney D-amino acid oxidase (DAAO) were from Sigma-Aldrich. FTO (fluorine-doped tin oxide) glass was purchased from Kinger (Wuhan, China).
[0044] Instruments: The morphology of the samples was characterized using a JSM-7001F field emission scanning electron microscope (FE-SEM). Transmission electron microscopy (TEM) and high-resolution transmission electron microscopy (HRTEM) images were obtained on a JEOL JEM-2100F high-resolution transmission electron microscope operating at 200 kV. Powder x-ray diffraction (XRD) analysis was performed using a PW3040 / 60 x-ray diffractometer. The x-ray photoelectron spectroscopy (XPS) under Al Kα x-ray radiation was measured using a Thermo Scientific photoelectron spectrometer. The absorption spectrum was recorded using a Shimadzu 3600plus UV-Vis-NIR spectrometer with barium sulfate as a reference. The fluorescence spectrum was excited by a 980 nm laser and measured using a fluorimeter (FLS1000, Ediburgh Instruments). Electrochemical impedance spectroscopy (EIS) tests were performed in a solution containing 1 mmol L -1 [Fe(CN)6] 3- / 4- and 0.1 mol L -1 KCl (amplitude 5mV, 10 -1 Up to 10 5 Hz) in a mixed solution. All photoelectrochemical (PEC) measurements were performed in an electrochemical workstation (CHI 760E, Shanghai Chenhua, China) with a standard three-electrode system, with the modified material fluorine-doped tin oxide (FTO) as the working electrode (the contact area of the working electrode was 0.64 cm2), a commercial Ag / AgCl electrode as the reference electrode, and a platinum wire as the counter electrode. 0.1 molL -1 Na2SO4 solution was used as the supporting electrolyte for PEC analysis. The detection unit used a MDL-Ш-980-2W near-infrared light source (Changchun New Industries, China) with a wavelength of 980 nm and a working potential of 0 V.
[0045] See attached Figure 1-10 The method for preparing a photoelectrochemical sensor based on a NYF-TiO2-Ti3C2 composite material provided in an embodiment of the present invention comprises the following steps:
[0046] (1) Multilayer Ti3C2T x Preparation: 1g Ti3AlC2 was slowly added to 20mL 49.0% hydrofluoric acid (HF) solution. The reaction mixture was stirred for 24h to ensure that Al was completely etched, and then the suspension was centrifuged, washed with deionized water to pH 7, and vacuum dried at 60℃ for 12h to obtain a multilayer Ti3C2T with an accordion structure. x .
[0047] (2) Few-layer Ti3C2T xPreparation: The multilayer Ti3C2T prepared in step (1) x Add to 20 mL of dimethyl sulfoxide (DMSO), stir continuously for 12 h, and ultrasonically strip for 1 h. Centrifuge the mixture and wash several times with deionized water to remove residual DMSO. Disperse the sample in 20 mL of deionized water, ultrasonically treat for 4 h under N2 protection, and then centrifuge at 5000 rpm for 20 min to remove the unstripped sample. Finally, the supernatant is set aside under N2 protection.
[0048] (3) Preparation of NYF-TiO2-Ti3C2 composite material: First, at 50°C, a mixture of RECl3 (8.0 mL, 0.1 M) consisting of YbCl3 6H2O, YCl36H2O, ErCl3 6H2O (molar ratio, Y:Yb:Er = 79.8:20:0.2) and polyethyleneimine (0.1 g) was added to ethanol (18 mL) and stirred for 40 min to obtain solution A. At the same time, NaF aqueous solution (10 mL, 0.2 mmol L 1) was dropped into the above mixture under vigorous stirring. Subsequently, the few-layer Ti3C2T x The supernatant was added to the mixture. After stirring again at 50°C for 50 min, the suspension was transferred to a 100 mL polytetrafluoroethylene-lined autoclave, heated at 200°C for 10 h, and finally washed three times with ultrapure water and ethanol (10000 rpm, 10 min), and dried in vacuo at 60°C for 12 h.
[0049] Comparative Example 1
[0050] For comparison, referring to the conditions of step (3) in Example 1, TiO2-Ti3C2 without doping with NaYF4:Yb / Er was synthesized without adding LnCl3 (YbCl3 6H2O, YCl3 6H2O, ErCl3 6H2O) and polyethyleneimine mixed solution.
[0051] Comparative Example 2
[0052] As a comparison, referring to the conditions of step (3) in Example 1, without adding a few layers of Ti3C2T x In the case of supernatant, NaYF4:Yb / Er without doping TiO2-Ti3C2 was synthesized.
[0053] Comparative Example 3
[0054] As a comparison, referring to the same process of Example 1, by adjusting the few-layer Ti3C2T x The added amount was used to prepare NYF-TiO2-Ti3C2 composite materials with ratios of 1:1, 1:2, 1:3, 2:1, 2:3, 3:1, and 3:2.
[0055] (4) Modification of NYF-TiO2-Ti3C2 composite electrode: The FTO slice was cleaned with 2.0M NaOH solution, ultrasonicated with acetone, ethanol, and ultrapure water, and dried with nitrogen. A 3M tape with holes (r = 4 mm, S = 50.265 mm2) was pasted on the electrode surface. Then, 30 μL of NYF-TiO2-Ti3C2 suspension (6 mg mL -1 , containing 4 μL 3mmol L -1 Thioglycolic acid) was dropped onto the FTO electrode and dried at room temperature to obtain the NYF-TiO2-Ti3C2 photoelectrochemical sensor. The modified electrode was slowly immersed in a mixture of EDC and NHS (weight ratio 3:2) at room temperature for 1 h, and then rinsed thoroughly with deionized water. 10 μL DAAO (4 mg mL -1 ) was coated on the surface of the electrode modified with NYF-TiO2-Ti3C2 and reacted at 4°C for 4 h. It was then rinsed with washing buffer to remove the physically adsorbed DAAO, and the NYF-TiO2-Ti3C2 / DAAO photoelectrochemical sensor was obtained.
[0056] Comparative Example 4
[0057] For comparison, referring to the preparation process of NYF-TiO2-Ti3C2 sensor in step (4) of Example 1, the modification material is replaced with NaYF4:Yb / Er to obtain a NaYF4:Yb / Er photoelectrochemical sensor.
[0058] Comparative Example 5
[0059] For comparison, referring to the preparation process of NYF-TiO2-Ti3C2 sensor in step (4) of Example 1, the modified material is replaced with TiO2-Ti3C2 to obtain a TiO2-Ti3C2 photoelectrochemical sensor.
[0060] Material characterization and performance testing application examples
[0061] (1) Analyze the samples using scanning electron microscopy (SEM) and transmission electron microscopy (TEM). SEM: Figure 1 The precursor Ti3AlC2 (a) in a medium block shape is etched with hydrofluoric acid to obtain a multilayer Ti3C2T with an accordion structure. x (b) After DMSO intercalation, few-layer Ti3C2T x(c); NaYF4:Yb / Er (d) obtained by hydrothermal reaction is a corn-like structure. TEM: The TEM image of TiO2-Ti3C2 (e) shows that TiO2 particles grow evenly on the Ti3C2 thin film; NYF-TiO2-Ti3C2 (f) shows that corn-like NaYF4:Yb / Er is evenly dispersed on the TiO2-Ti3C2 thin film; HRTEM: The lattice fringes of NaYF4:Yb / Er (h) are clearly visible, indicating that the material has a high degree of crystallinity; The mapping elements in NYF-TiO2-Ti3C2 (I) are clearly visible, further proving that the composite material was successfully synthesized.
[0062] (2) The crystal structure of NYF-TiO2-Ti3C2 was analyzed by XRD. Figure 2 As shown, two characteristic peaks appear at 25.3 and 37.7 in curve c, corresponding to the (101) and (004) crystal planes of rutile TiO2 (JCPDS No. 65-5714), further indicating that the product obtained by solvothermal reaction in a mixed solution of ethanol and water is TiO2-Ti3C2. In addition, the XRD pattern of the NYF-TiO2-Ti3C2 composite material (curve c) is consistent with the hexagonal NaYF4:Yb / Er crystal plane (curve a, JCPDS No 16-0334) and the crystal plane of TiO2-Ti3C2, indicating that the composite material prepared by the solvothermal method is composed of NaYF4:Yb / Er and TiO2-Ti3C2, and no impurity peaks are generated.
[0063] (3) XPS was used to further verify the composition of NYF-TiO2-Ti3C2. Figure 3 The full spectrum in A shows that all elements exist in a single structure, proving the successful synthesis of NYF-TiO2-Ti3C2 nanosheets. In addition, no Al (Al 2p) peak was found in either sample, further indicating that the Al of the precursor was completely etched. In the Ti 2p high-resolution spectrum (Figure 3B), the peak centers in NYF-TiO2-Ti3C2 and TiO2-Ti3C2 are 458.88 (464.27) eV and 459.90 (465.36) eV, respectively, belonging to Ti 4+ 2p3 / 2(Ti 4+ 2p1 / 2), indicating that TiO2 is formed by a solvothermal reaction. Compared with the original TiO2-Ti3C2, the binding energy of Ti 2p in the NYF-TiO2-Ti3C2 composite is significantly shifted to a lower energy level, indicating that the electron density of TiO2-Ti3C2 is increased and a heterojunction is formed between NaYF4:Yb / Er and TiO2-Ti3C2.
[0064] (4) The conductivity of the material was studied using EIS. Figure 4 Among them, the arc diameter of NYF-TiO2-Ti3C2 (curve c) is the smallest, indicating that the composite material has a lower electron transfer resistivity and better conductivity. However, due to the steric hindrance caused by the addition of DAAO, the resistance of NYF-TiO2-Ti3C2 / DAAO (curve d) is larger, proving that each step of electrode modification is successful.
[0065] (5) The samples were analyzed using UV-visible-near infrared diffuse reflectance. Figure 5 The UV-Vis-NIR spectra of NaYF4:Yb / Er, TiO2-Ti3C2, and NYF-TiO2-Ti3C2 are shown in Figure 1. It can be seen from the figure that TiO2-Ti3C2 has full-band absorption, but the absorbance is weak. After combining with NaYF4:Yb / Er, the absorbance of the NYF-TiO2-Ti3C2 composite material increases significantly, proving that the material is successfully composited.
[0066] (6) The luminescence characteristics of the samples were further studied using fluorescence spectroscopy. Figure 6 As shown in the figure, under 980 laser irradiation, NaYF4:Yb / Er has a strong upconversion emission, with three typical emission peaks at 525nm, 542nm and 657nm, corresponding to Er 3+ of 4 H 11 / 2 → 4 I 15 / 2 , 4 S 3 / 2 → 4 I 15 / 2 ,and 4 F 9 / 2 → 4 I 15 / 2 After modification with TiO2-Ti3C2, the composite material NYF-TiO2-Ti3C2 has obvious fluorescence quenching phenomenon, indicating that the energy of NaYF4:Yb / Er can be effectively transferred to TiO2-Ti3C2 nanosheets, further improving the light conversion efficiency.
[0067] (7) Photocurrent test: A three-electrode system was used, with the modified NaYF4:Yb / Er, TiO2-Ti3C2, NYF-TiO2-Ti3C2, NYF-TiO2-Ti3C2 / DAAO photoelectrochemical sensors as working electrodes, platinum wire as counter electrode, and silver / silver chloride as reference electrode. The photocurrent was tested under irradiation with a 980nm laser light source using 0.1M Na2SO4 as buffer solution and an applied voltage of 0V. The average value was taken after three repetitions. The photocurrent calculation formula is: ΔI = I sample –Iblank (I blank : Background current, i.e., the photocurrent of the buffer only; I sample : contains the photocurrent of the object being measured). Figure 7 Figure 2: Photocurrent responses of photoelectrochemical sensors modified with NaYF4:Yb / Er (a), TiO2-Ti3C2 (b), NYF-TiO2-Ti3C2 (d), and NYF-TiO2-Ti3C2 / DAAO (c, e). NaYF4:Yb / Er (a), TiO2-Ti3C2 (b), NYF-TiO2-Ti3C2 / DAAO (c), and NYF-TiO2-Ti3C2 (d) are photocurrents without the addition of target substance D-ser, and NYF-TiO2-Ti3C2 / DAAO (e) is the photocurrent with the addition of 417.0 μmol L -1 The photocurrent of the composite material NYF-TiO2-Ti3C2 (d) is significantly higher than that of the single materials NaYF4:Yb / Er (a) and TiO2-Ti3C2 (b), indicating that the electron-hole transmission speed of the composite material increases, the electrical signal is enhanced, and after modification with DAAO, it has a specific response to D-ser.
[0068] (8) Photoelectrochemical sensor anti-interference test: In the presence of 123.46 μmol L -1 In the D-ser system, according to the distribution characteristics of the interference concentration, 10 times of D-aspartic acid, L-serine, dopamine (DA), L-proline, L-glutamic acid, L-lysine, glutathione (GSH), L-threonine, glucose, ascorbic acid (AA), L-histidine and 100 times of Na + , K + Mg 2+ , Ca 2+ Interference with the photocurrent response of the D-ser detection system, such as Figure 8 The results show that the sensing platform exhibits high selectivity for D-ser and has excellent anti-interference performance.
[0069] (9) Photocurrent response of photoelectrochemical sensor to different concentrations of D-ser: The photocurrent change of NYF-TiO2-Ti3C2 / DAAO photoelectrochemical sensor to different concentrations of D-ser was tested, and the following results were obtained: Fig. 9 The photocurrent change (A) and linear relationship diagram (B) are shown. The detection range is: 2μmol L -1 ~1650 μmol L -1 The detection limit is as low as 0.286 μ mol L -1, the linear equation is ΔI = 313.5log C[D-ser]-335.2(R 2 =0.998; n=3).
[0070] (10) Photoelectrochemical sensor stability test: Fig.10 As shown, in the presence of 59.77 μmol L -1 In the D-ser system, the light was turned on and off continuously for 420 s, and no obvious photocurrent drop was observed, which indicated that the NYF-TiO2-Ti3C2PEC biosensor had significant stability in D-ser determination.
[0071] (11) Actual sample detection: The actual samples detected by the present invention are human serum and artificial cerebrospinal fluid. As shown below, Table 1 and Table 2 are the analysis results of adding D-ser to the actual samples of human serum and artificial cerebrospinal fluid, respectively. The results show that the recovery rates of the two samples at different concentrations are very high, the relative standard deviations are low, and the precision and accuracy are very good.
[0072] Table 1 Analysis of D-ser content in human serum
[0073] Addition amount (μM) Detection amount after addition (μM) Relative standard deviation (%) Recovery rate (%) 10 10.26±0.40 3.94 102.56 20 20.01±0.27 1.32 100.04 40 40.17±0.42 1.06 100.43
[0074] Table 2 Analysis of D-ser content in artificial cerebrospinal fluid
[0075] Addition amount (μM) Detection amount after addition (μM) Relative standard deviation (%) Recovery rate (%) 20 20.55±0.54 2.68 102.74 40 40.45±2.65 6.63 101.13 80 73.50±3.57 4.47 91.88
[0076] The above-mentioned embodiment of the present invention, through the modification of the composite material electrode and the application of the photoelectrochemical sensor, up-converts the NYF-TiO2-Ti3C2 composite material, using corn-shaped NaYF4:Yb / Er as the energy donor, and can convert near-infrared light into visible light that matches the absorption of TiO2-Ti3C2, thereby solving the problems of low light utilization between the up-conversion material and the semiconductor, easy recombination of photogenerated carriers and poor stability.
[0077] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. Application of photoelectrochemical sensor based on upconversion NaYF4:Yb / Er-TiO2-Ti3C2 (NYF-TiO2-Ti3C2) composite material in detecting D-Ser, characterized in that: Includes the following: The preparation method of the photoelectrochemical sensor comprises the following steps: Step 1: Multilayer Ti3C2T x The powder was added to a dimethyl sulfoxide solution and stirred. The mixed solution after the reaction was centrifuged and washed to obtain a few-layer Ti3C2T x ; Step 2: Prepare NYF-TiO2-Ti3C2 composites by solvothermal method; Step 3: Modification of NYF-TiO2-Ti3C2 composite electrode.
2. The use of the photoelectrochemical sensor based on the NYF-TiO2-Ti3C2 composite material in detecting D-Ser according to claim 1, characterized in that: The first step is to prepare a few-layer Ti3C2T x The preparation method is as follows: multilayer Ti3C2T x The powder was added into dimethyl sulfoxide solution and stirred for 12 h, and then the mixed solution after the reaction was centrifuged and washed to obtain a few-layer Ti3C2T x .
3. The use of the photoelectrochemical sensor based on the NYF-TiO2-Ti3C2 composite material in detecting D-Ser according to claim 2, characterized in that: The few-layer Ti3C2T x Before use, it needs to be dispersed in deionized water, sonicated under N2 protection, and then centrifuged to remove the undetached sample and keep the supernatant under N2 protection for later use.
4. The use of the photoelectrochemical sensor based on the NYF-TiO2-Ti3C2 composite material in detecting D-Ser according to claim 1, characterized in that: The preparation method of the NYF-TiO2-Ti3C2 composite material comprises the following steps: S1: Add YbCl3 6H2O, YCl3 6H2O, ErCl3 6H2O and polyethyleneimine into ethanol and stir to obtain solution A; S2: Then the sodium fluoride solution and the few-layer Ti3C2T x Solution A was added to the solution; S3: The mixture is then stirred evenly and subjected to a solvent thermal reaction. The mixed solution obtained after the reaction is centrifuged, washed and dried to prepare a NYF-TiO2-Ti3C2 composite material.
5. The use of the photoelectrochemical sensor based on the NYF-TiO2-Ti3C2 composite material in detecting D-Ser according to claim 4, characterized in that: The molar ratio of YbCl3 6H2O, YCl3 6H2O and ErCl3 6H2O is 79.8:20:0.
2.
6. The use of the photoelectrochemical sensor based on the NYF-TiO2-Ti3C2 composite material in detecting D-Ser according to claim 4, characterized in that: The solvent thermal reaction conditions were 220 °C and the reaction time was 10 h.
7. The use of the photoelectrochemical sensor based on the NYF-TiO2-Ti3C2 composite material in detecting D-Ser according to claim 1, characterized in that: The modification of the electrode in the third step includes the following: ultrasonically dispersing the NYF-TiO2-Ti3C2 composite material, drop-coating it on clean fluorine-doped indium tin oxide conductive glass, and drying it at room temperature.
8. The use of the photoelectrochemical sensor based on the NYF-TiO2-Ti3C2 composite material in detecting D-Ser according to claim 4, characterized in that: The washing and drying conditions in S3 are washing with deionized water and ethanol, and then placing in a vacuum drying oven at 60° C. for 12 h.
9. The use of the photoelectrochemical sensor based on the NYF-TiO2-Ti3C2 composite material in detecting D-Ser according to claim 7, characterized in that: The indium tin oxide conductive glass is cleaned with washing powder, acetone, ethanol and ultrapure water in sequence, and then blown dry with nitrogen.
Citation Information
Patent Citations
Near-infrared photocatalytic electrode, and preparation method and application thereof
CN112382510A
Preparation and application of up-conversion tin dioxide coated perovskite electrode
CN113176312A